Surface Roughness in Metal Material Extrusion 3D Printing: The Influence of Printing Orientation and the Development of a Predictive Model - Van, Cuong Nguyen; Hoang, Anh Le; Long, Cao Dang; Hoang, Duy Nguyen (Engineering, Technology & Applied Science Research, 2023)
This study investigates the influence of printing orientation on the surface roughness in metal material extrusion 3D printing of 17-4 PH stainless steel. Experimental tests were conducted on the Markforged Metal X commercial 3D printer at Vinh Long University of Technology Education, Vietnam. The samples were printed in three different orientations: flat, on-edge, and upright. Surface roughness measurements were performed using a handheld Mitutoyo SJ-210 roughness tester. Quantitative analysis of the surface roughness measurements revealed significant variations among the different printing orientations. The upright orientation exhibited the smoothest surface, with an average Ra value of 7.42 μm and Rz value of 40.49 μm. In contrast, the flat orientation showed the highest roughness, with an average Ra value of 82.83 μm and Rz value of 109.32 μm. The on-edge orientation had intermediate roughness values, with an average Ra value of 69.42 μm and Rz value of 92.17 μm. The study also introduces a novel predictive model for surface roughness based on the printing parameters. The model demonstrated accurate estimations for surface roughness values in specific cases, enabling optimization of the printing process for desired surface quality.